Growth, Mortality, Exploitation Rate, and Recruitment of Blood Clam (Anadara granosa) in the Rangsang Barat Waters, Riau Province (Jurnal Natur Indonesia, 2023)
Growth, mortality, exploitation rate, and recruitment of Anadara granosa cockle in Rangsang Barat coastal waters were studied from July to October  2019. The objective of this research was to study the growth, mortality, exploitation rate, and recruitment of A.granosa cockle. Sampling was done monthly at three main stations. The cockle collected from plot 1 x 1 m2  on quadrat transect. The result showed that the asymptotic length (L∞) of A.granosa was 30.45 mm, the annual growth coefficient (K) was 0.83 per year, the total mortality (Z) was 4.46 per year, natural mortalities (M) were 1.60 per year, and fishing mortalities (F) was 2.86 per year. The rate of exploitation (E = 0.64) of blood clams in Rangsang Barat waters has begun to threaten sustainability. The recruitment occurred every month, the peaks occurred in July  (13.83 %), and August (13.08 %).